Jokes as political satire: a semiotic engagement with caricatured images of ZANU PF leader Robert Mugabe and MDC-T leader Morgan Tsvangirai on facebook page Zim Jokes Corner during 2013 election period - Moyo, Priscilla N. (Midlands State University, 2014)
In a country with stringent media laws infringing freedom of expression, speech and assembly, alternative forms of communication like Zim Jokes Corner, a Facebook page have created a democratic space for citizens to interact, air their different views and debate over Zimbabwe politics especially the major presidential candidates ZANU PF leader Robert Mugabe and MDC-T leader Morgan Tsvangirai during the 2013 elections. The study is informed by qualitative research specifically archival research which contains the caricatured images of Mugabe and Tsvangirai and these were gathered using purposive and convenience sampling. For analyzing these caricatured images the researcher used semiotic analysis, discourse analysis and content analysis as a way to interpret and attach meaning to the caricatured images as well as to the discourses used by Zim Jokes Corner readers. Jokes in the form of caricatured images were used by Zim Jokes Corner as means to communicate political messages. It has been discovered that when people are engaging with these caricatured images they use their personal experiences as well as their political backgrounds to attach meaning to the caricatured images portraying Mugabe and Tsvangirai. These jokes are viewed as political satire as they ridicule, castigate and mock the leadership qualities of Mugabe and Tsvangirai. Mugabe is portrayed as a dictator ruling with an iron fist hand and he is ridiculed for being in power for 34 years, he is criticized for being a war lord that cannot be defeated in any circumstance, his championship in the political game is questioned as he is mocked for rigging elections. Tsvangirai on the other hand is mocked for having low stamina and that has reduced him to an orange peel as he is castigated of being a “puppet” of the West, after his defeat in the 2013 elections he is reduced from hero to zero as he is portrayed as a herd man in Buhera. Zim Jokes Corner has managed to mediate for the masses about Zimbabwean politics through caricatured images which are understood by everyone as images say a lot more than thousand words. Zim Jokes Corner as a platform that breaks physical boundaries and the constraints of space and time has enabled citizens to exercise their rights to freedom of speech, expression and assembly.